The Challenge of Maintaining Local Culture in the Global Era (Case Study of the RT Culture Competition, RT 4, Cemandi Village, Sedati District, SidoarjoRegency) - Nirwasita Sakhi Azzahra (Jurnal Ilmiah Mandala Education (JIME), 2025)
Introduction: This study examines the challenges of preserving local culture in the era of globalization by focusing on the Cultural Neighborhood Competition (Lomba RT Berbudaya) in RT 4, Cemandi Village, Sedati Subdistrict, Sidoarjo Regency. The phenomenon of globalization, digital transformation, industrialization, and decreasing open spaces poses significant threats to cultural sustainability. The competition serves as a community-based initiative aimed at both strengthening social solidarity and preserving cultural values.Material and Methods: The research employed a descriptive qualitative approach, with data collected through interviews with the head of RT 4 and representatives from the Community and Village Empowerment Agency (DPMD). To ensure validity and reliability, data were analyzed using source triangulation. The theoretical framework is based on concepts of social solidarity, mutual cooperation, communal harmony, and the role of community participation in cultural preservation.Research Results: Findings indicate that the Cultural Neighborhood Competition has a dual role: functioning as a contest and as a medium for fostering community cohesion. Traditional values such as mutual cooperation (gotong royong), communal harmony (guyub rukun), and togetherness were identified as essential drivers of the event’s success, encouraging active participation, collective responsibility, and a sense of belonging. Moreover, the program supports the preservation of local arts and traditions, including patrol music, banjari, PKK women’s gatherings, and the Reog Cemandi performance, which has become a cultural identity of the local community.Conclusion: The study concludes that the Cultural Neighborhood Competition is not merely ceremonial but serves as a strategic effort to strengthen social solidarity, revive traditional values, and safeguard local identity amidst the challenges of modernization and globalization.